Karakteristik Sensori Otak-Otak GreenFish Dengan Proporsi Ikan Patin Dan Ikan Bandeng Dengan Penambahan Brokoli - Salam, Muhamad Akbar Maulana Moelya; Any Sutiadiningsih; Niken Purwidiani; Ila Huda Puspita Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Otak-otak is a traditional Indonesian food made from fish meat as its main ingredient. The author investigated the effects of different ratios of catfish and milkfish (80:20, 70:30, 60:40) combined with varying amounts of broccoli (10%, 20%, 30%) on the sensory characteristics, panelist preference levels, and nutritional content of GreenFish otak-otak. Sensory characteristic testing was conducted using an instrument comprising attributes of color, taste, aroma, texture, and shape, rated on a 1-5 scale. Hedonic testing was also performed to assess liking levels on a 1-5 scale. The optimal ratio from the analysis of the two tests above will undergo nutritional content (proximate) testing to determine carbohydrate, protein, fat, and beta-carotene content. The results of the analysis using the two-way ANOVA method showed a significant effect on the attributes of color, taste, aroma, and texture. However, the attribute of shape did not show a significant effect. The formulation (60:40)20% (P3S2) obtained the highest sensory test and liking scores. This formulation was proven to improve quality, liking, and nutritional value.